PENGARUH PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP KESEJAHTERAAN MASYARAKAT KABUPATEN BERAU - Lisa Puspita Sari (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The purpose of this study is to investigate the impact of infrastructure development on community welfare in Berau Regency. The sample collection method employed in this study is non-probability sampling, with samples selected randomly using a purposive sampling technique. Data collection methods include literature reviews and documentation. The results of the study indicate that infrastructure development significantly influences community welfare in Berau Regency. This is evidenced by the t-table value of 2.57058 being less than the t-count value of 5.370.